2019
DOI: 10.1016/j.matchar.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

3D-SEM height maps series to monitor materials corrosion and dissolution

Abstract: An accurate method for the characterization of the topographic evolution of materials during dissolution at the submicrometric scale is reported. This method is based on the recording of Environmental SEM tilted images of a selected zone at the surface of a sample for various dissolution times. After each observation, a 3D surface reconstruction was made leading to a series of height maps of the selected zone of interest. One 3D reconstruction was compared to an AFM image of the same zone in order to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Grain and phase boundaries in ceramics and rocks are another source of defects and become important in dissolutions as the grain size decreases below the submicrometer scale. The excess free energy from the interfacial energy is expected to enhance the grain boundary dissolution as a number of experiments have suggested [67,68,69,70]. Dissolution at the boundaries may penetrate to a great depth assisted by the enhanced dissolution kinetics if the transport of reactive species within gain boundaries is not the rate-determining step.…”
Section: Effect Of the Structure Of Oxides On Chemical Durabilitymentioning
confidence: 99%
“…Grain and phase boundaries in ceramics and rocks are another source of defects and become important in dissolutions as the grain size decreases below the submicrometer scale. The excess free energy from the interfacial energy is expected to enhance the grain boundary dissolution as a number of experiments have suggested [67,68,69,70]. Dissolution at the boundaries may penetrate to a great depth assisted by the enhanced dissolution kinetics if the transport of reactive species within gain boundaries is not the rate-determining step.…”
Section: Effect Of the Structure Of Oxides On Chemical Durabilitymentioning
confidence: 99%
“…During the leaching experiment, the surface of the pellet was also regularly observed under environmental conditions. According to Podor et al 42 , the pellet was directly introduced in the ESEM chamber equipped with a Peltier stage without any further preparation. The Peltier stage was cooled down to 2 °C prior the introduction of the sample.…”
Section: Characterizations Of Uo 2 Pelletmentioning
confidence: 99%
“…The surface area of each of these two investigated zones was S image = 552 µm². ESEM-optimized images were recorded using the conditions optimized by Podor et al 38…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, the heterogeneous evolution of the microstructure of the pellet under these conditions allowed to obtain better 3D reconstruction accuracy. Indeed, Podor et al 38 showed that the greater the height differences at the surface of the pellet, the smaller the errors on the height maps. A selection of ESEM images recorded in the zone of interest at the surface of UO 2 + 3 mol.% PGMs pellet dissolved in 0.1 mol.L -1 HNO 3 at 60°C, with a tilt angle of 0° and at the highest magnification, is provided in Figure S2.…”
Section: Quantitative Monitoring Of Pellet Microstructure Changes Durmentioning
confidence: 99%